Math, asked by apeksha252, 6 months ago

Factorise :
(x+y)²(x-y) ²​

Answers

Answered by poojithashankar2008
4

evaluate : ( x ² - y ² ) ²

expand : x⁴ + y⁴ - 2 ( xy ) ²

Answered by Anonymous
1

Answer:

\huge\colorbox{yellow}{Answer\:-}

\small\underbrace\mathrm\red{Using\:formula}

 \boxed{ {a}^{2} -  {b}^{2} = (a + b)(a - b)}

Now,

 {(x + y)}^{2} -  {(x - y)}^{2}

 = ( {x}^{2}  + 2xy +  {y}^{2}) - ( {x}^{2} - 2xy +  {y}^{2})

 =  {x}^{2} + 2xy +  {y}^{2} -  {x}^{2} + 2xy -  {y}^{2}

 = 2xy + 2xy

\boxed{\pink{ =  > 4xy}}

\huge\colorbox{yellow}{Thank\:You}

Similar questions